BLOOD TRANSFUSIONS IN THE MANAGEMENT OF THOSE INJURED: IMPACT ON THE COURSE OF WOUND DISEASE (REPORT ONE) - I. M. Samokhvalov; S. N. Nedomolkin; S. A. Smirnov; S. V. Gavrilin; V. I. Badalov; D. P. Meshakov; V. V. Suvorov; K. P. Kuneev (Вестник анестезиологии и реаниматологии, 2018)
The acute severe blood loss is one of the leading causes of mortality of the wound disease in its first period, i.e. wound shock. The potential negative impact of blood transfusions on the course of wound disease in the wounded with acute severe blood loss is not significantly expressed. In the wounded with acute massive blood loss at the extremely severe degree the development of life threatening conditions related also to blood transfusion is mostly defined by the tactics of blood transfusion therapy in the post shock period of wound disease.